The reciprocal relationship between depressive symptoms and deliberate self-harm among Chinese rural adolescents: a cross-lagged panel analysis - Qijiao Liu; Xiaohe Xu; Jianjun Jiang; Wei Peng; Yuanyi Ji; Ruixi Yang; Ming Zhang; Shiying Li; Yuchen Li; Qiaolan Liu (Frontiers Media S.A., 2024)
BackgroundWhile the association between depressive symptoms and deliberate self-harm in adolescence is extensively documented, the nature, bi-directionality, and longitudinal dynamics of this relationship remain underexplored. This study aims to investigate the causal and reciprocal relationship between depressive symptoms and deliberate self-harm among rural adolescents in western China.MethodsA 2-year panel study was conducted among 1,840 adolescents aged 10-18 attending rural junior and senior high schools in Sichuan Province, China. The Center for Epidemiologic Studies-Depression Scale (CES-D) and a global measure of self-reported deliberate self-harm were utilized to examine the relationship between depressive symptoms and deliberate self-harm using both classic and random intercept cross-lagged panel models. Multi-group comparisons were carried out for the gender, pubertal stage, and academic performance subgroups.ResultsPositive and statistically significant correlations were found between depressive symptoms and deliberate self-harm both within and across the three waves of the panel survey, after adjusting for covariates, among rural adolescents in western China (Range: 0.05-0.28, p < 0.05). As anticipated, depressive symptoms positively predicted later deliberate self-harm, which in turn reciprocally predicted subsequent depressive symptoms, both between and within individuals. While the cross-lagged effects were invariant by gender and academic performance, the effect of baseline depressive symptoms on later deliberate self-harm was stronger for adolescents in the early pubertal stage (β = 0.19, 95% Confidence Interval: 0.08 to 0.30) than for those in the middle-to-late pubertal stage (β = 0.13, 95% CI: 0.06 to 0.19).ConclusionThere is a causal and reciprocal relationship between depressive symptoms and deliberate self-harm among rural adolescents in China. Not only does this finding lend further credence to a growing body of research on adolescents' self-harming behaviors but also informs early intervention strategies aimed at improving behavioral health of rural adolescents in western China.